Pulmonary Diseases and Periodontal Health- A Review - Bhardwaj, Dr. Vinay Kumar; Fotedar, Dr. Shailee; Negi, .Dr. Nishant; Chauhan, Dr. Atul (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The oral cavity has a multitude of functions in relation to daily life. The poor health has thepotential of affecting the quality of life. In recent years, efforts have been made to recognizeoral health as an integral part of overall health. The anatomical continuity between the lungsand the oral cavity makes the latter a potential reservoir of respiratory pathogens. The microorganismsmay enter the lung by inhalation, but the most common route of infection isaspiration of what pneumologists have long referred to as oropharyngeal secretions. There isa fair evidence exists between respiratory disorders and poor oral hygiene & good evidenceexist that improved oral health and professional oral health care reduce the progression oroccurrence of respiratory diseases among high risk adults. Dental plaque can act as areservoir for respiratory infections. Microorganisms can be released from the dental plaque into salivary secretions, which are then aspirated into lower respiratory tract to causerespiratory diseases like pneumonia and chronic obstructive pulmonary disease. Periodontaldiseases and respiratory diseases including bronchial asthma have an inflammatory naturethus mandates a positive correlation between these. This paper discusses the relation betweenthe periodontitis, its influence on the incidence of respiratory disorders and underlines theimportance of improving oral hygiene among patients who are at risk.